A fish out of water? Survival of seafood products from developing countries in the EU market. (May 2019) - Zhang, Dengjun; Tveterås, Ragnar
Abstract: This article uses a duration analysis and commodity-level data to examine the trade performance of seafood products from developing countries in the EU market. Among the determinants of trade longevity, the EU Generalized Scheme of Preferences (GSP) granted to developing countries is of particular interest in this study. The empirical results show that the GSP has a significant impact on the trade duration of seafood products from developing countries, although with substantial differences across preferential trade areas and product types. GSP prolongs trade duration for processed products but not for unprocessed products, indicating that the scheme and increasing globalization have improved trade performance of value-added seafood products from developing countries. This probably contributes to a sustainable use of aquatic resources and continuous seafood export growth for those countries.